An Overview of Inertia Emulation Strategies for DC Microgrids: Stability Analysis and AC Microgrid Analogies - Mahdis Haddadi; Saman A. Gorji; Samson S. Yu (IEEE Open Journal of the Industrial Electronics Society)
Inertia is a critical factor in maintaining the frequency stability of power systems. However, the growing integration of power electronics-based renewable energy sources (RESs) has significantly reduced system inertia. AC and dc microgrids have emerged as key solutions for integrating RESs. Unlike traditional synchronous generators, power electronic converters interfacing RESs lack inherent inertia and damping, posing challenges to the control and stability of these microgrids. To address these challenges, virtual inertia control strategies, which emulate the behavior of synchronous generators, have been widely adopted to enhance the stability of ac microgrids. Drawing on the analogies between ac and dc systems, similar virtual inertia concepts have been extended to dc microgrids, demonstrating their potential to improve system stability. This article provides a comprehensive review of inertia enhancement strategies for dc microgrids, examining their key features, benefits, and limitations. The analogy between synchronous generators/dc machines and energy storage systems is explored, with a particular focus on the implementation of virtual inertia and damping control in energy storage converters as a promising solution to mitigate power fluctuations. In addition, this article investigates the grid-forming and grid-following converter analogies in ac and dc microgrids. Various stability analysis methods applied to inertia enhancement strategies are also reviewed, offering readers a comprehensive understanding of the current state of research. By addressing the conceptual and technical analogies between ac and dc systems, this review aims to provide valuable insights for developing advanced control strategies for next-generation microgrids.